How to sell not just space, but time. - Dunn, Will (New Statesman, 2019)
The article discusses business operations and performance of shared workspace provider WeWork. Topics explored include the office desk and space being offered by the firm to start-ups, freelancers, and remote workers, the availability of WeWork office spaces in various cities such as London, England and New York City, and the outcome of the initial public offering (IPO) plans of the company.